Optimal coordinated operation of integrated energy hubs, considering regenerative braking utilization - Saeed Akbari; Seyed Saeed Fazel; Shahram Jadid (IET Electrical Systems in Transportation)
Abstract This article presents a coordinated operation model for energy management of a multi‐integrated energy system based on Mixed‐Integer Linear Programing (MILP). The power derived by trains from regenerative braking energy (RBE), during deceleration, is utilised to meet the interconnected energy hubs’ (IEHs) demand. The recovered energy is calculated by simulating the motion of the trains in MATLAB software. The electricity and heat demand response (DR) programs are integrated into the proposed model to study their impacts on the operating cost and the carbon emission of the IEH, considering several case studies. Furthermore, the uncertainties of the RBE, photovoltaic power generation, and loads of the IEH are considered by formulating the optimisation problem stochastically through a scenario‐based approach. Therefore, a scenario generation and reduction decision‐making technique is employed. Finally, the GAMS optimisation software is used to assess the efficiency of the presented MILP model. The simulation results indicate that the total operating cost of the IEH reduced 2.0% and 1.4% in the case studies. Also, the CO2 emission is decreased by about 0.3% by applying the coordination scheme besides the DR programs.